2017
DOI: 10.1002/jmor.20712
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for convergent evolution of a neocortex‐like structure in a late Permian therapsid

Abstract: The special sensory, motor, and cognitive capabilities of mammals mainly depend upon the neocortex, which is the six-layered cover of the mammalian forebrain. The origin of the neocortex is still controversial and the current view is that larger brains with neocortex first evolved in late Triassic Mammaliaformes. Here, we report the earliest evidence of a structure analogous to the mammalian neocortex in a forerunner of mammals, the fossorial anomodont Kawingasaurus fossilis from the late Permian of Tanzania. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 108 publications
5
52
0
Order By: Relevance
“…The reason for this change remains unclear but may be related to an increase in body mass through time (Finarelli & Flynn ). In contrast, Laaß & Kaestner () found that a fossorial Permian therapsid had a higher EQ compared to other members of the group; however, the authors did not consider locomotor mode of the therapsids to which they made their comparisons, making it difficult to pinpoint fossoriality as the cause of their taxon's relatively large brain size.…”
Section: Discussionmentioning
confidence: 95%
“…The reason for this change remains unclear but may be related to an increase in body mass through time (Finarelli & Flynn ). In contrast, Laaß & Kaestner () found that a fossorial Permian therapsid had a higher EQ compared to other members of the group; however, the authors did not consider locomotor mode of the therapsids to which they made their comparisons, making it difficult to pinpoint fossoriality as the cause of their taxon's relatively large brain size.…”
Section: Discussionmentioning
confidence: 95%
“…1 and 2), which was according to Castanhinha et al (2013) a specimen of Diictodon feliceps. There is also evidence for the unossified zone in the anomodont Pristerodon mackayi (Laaß, 2015), but it seems to be absent in Niassodon mfumukasi (Castanhinha et al, 2013) and in K. fossilis (Laaß and Kaestner, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…On the one hand, this is caused by the fact that therapsids did not possess a completely ossified endocranial cavity, whereas on the other hand it seems likely that most parts of the small, tubular brain were obviously not in close contact with the brain cavity (Hopson, 1979;Kemp, 2009). An exception might be the endocranial cavity of Kawingasaurus fossilis, which is almost completely ossified and due to the presence of impressions of soft-tissue structures in the braincase it seems reasonable that at least some parts of the enlarged brain were in close contact with the endocranial cavity (Laaß and Kaestner, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The endocranial morphology of R. procurvidens resembles the plesiomorphic pattern retained in most therapsids. Disparate endocast morphologies seem to be a consequence of cranial specializations and ecological variations: the inner ear morphology (plus stapes fitting) of Pristerodon suggests adaptations of the auditory apparatus and a higher sensitivity to airborne vibrations (Laaß, , ), whereas the brains of the cistecephalids Kawingasaurus and Cistecephalus are especially distinctive and reflect a fossorial lifestyle, with Kawingasaurus even presenting a convergent neocortex‐like structure, as suggested by Laaß & Kaestner ().…”
Section: Discussionmentioning
confidence: 89%
“…It is underdeveloped in R. procurvidens , being elliptically shaped and almost straight in the longitudinal axis. In this aspect, it resembles the horizontal canal of K. fossilis (Laaß, ; Laaß & Kaestner, ), differing from Niassodon mfumukasi (Castanhinha et al ) and P. mackayi (Laaß, ), which have a wider and more rounded horizontal semicircular canal (Fig. ).…”
Section: Discussionmentioning
confidence: 93%